Regulating the production of (R)-3-hydroxybutyrate in Escherichia coli by N or P limitation - Guevara-Martínez, Mónica; Sjöberg Gällnö, Karin; Sjöberg, Gustav; Jarmander, Johan; Pérez-Zabaleta, Mariel; Quillaguamán, Jorge; Larsson, Gen (Frontiers in Microbiology, 2015)
The chiral compound (R)-3-hydroxybutyrate (3HB) is naturally produced by many wild type organisms as the monomer for polyhydroxybutyrate (PHB). Both compounds are commercially valuable and co-polymeric polyhydroxyalkanoates have been used e.g. in medical applications for skin grafting and as components in pharmaceuticals. In this paper we investigate cultivation strategies for production of 3HB in the previously described E. coli strain AF1000 pJBGT3RX. This strain produces extracellular 3HB by expression of two genes from the PHB pathway of Halomonas boliviensis. H. boliviensis is a newly isolated halophile that forms PHB as a storage compound during carbon excess and simultaneous limitation of another nutrient like nitrogen and phosphorous. We hypothesize that a similar approach can be used to control the flux from acetyl-CoA to 3HB also in E. coli; decreasing the flux to biomass and favouring the pathway to the product. We employed ammonium- or phosphate-limited fed-batch processes for comparison of the productivity at different nutrient limitation or starvation conditions. The feed rate was shown to affect the rate of glucose consumption, respiration, 3HB and acetic acid production, although the proportions between them were more difficult to affect. The highest 3HB volumetric productivity, 1.5 g L-1 h-1, was seen for phosphate-limitation.